Radiation protection paint and method for producing the same
Patent Information
- Application Number
- CN202611218540.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明针对现有含PVA的高固含量射线防护涂料中,成膜所需的整体强碱性环境(pH>10.0)与医用安全pH范围(4.5~8.5)之间存在的矛盾,以及高固含量(≥70wt%)下涂层易发生干燥开裂的问题,提供了一种防辐射涂料及其制备方法
1)本发明的防辐射涂料,为一种高固含量防辐射涂料,尤其适用于医用射线防护敷料、介入手术用局部辐射屏蔽涂层,以及核设施防护涂层领域。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of radiation protection materials technology, and in particular to a radiation-shielding coating and its preparation method. Background Technology
[0002] Medical radiation shielding coatings are a class of functional materials that disperse heavy metals or heavy element compounds with X-ray absorption capabilities (such as bismuth oxide, bismuth tungstate, barium sulfate, etc.) in a polymer film-forming matrix, and then dry rapidly after coating to form a flexible shielding film. Polyvinyl alcohol (PVA) is widely used as the film-forming matrix material for this type of coating due to its excellent film-forming properties, good bioadhesion, and ability to be combined with various inorganic fillers.
[0003] In practical clinical applications, to achieve sufficient radiation shielding efficiency, the solid filler content (i.e., solid content) in the coating typically needs to reach above 70 wt%. However, through long-term research, the inventors have discovered that in composite systems containing PVA, oxide ceramic particles (such as zirconium oxide, tungsten oxide, gadolinium oxide, and bismuth oxide), and heavy metal fillers, the film-forming properties deteriorate sharply when the total solid content exceeds 70 wt%. After coating and drying, the rapid evaporation of the solvent generates enormous capillary shrinkage stress within the film layer. Combined with the physical obstruction of PVA molecular chain movement by the high content of rigid filler particles, this leads to the film layer easily developing dense, penetrating microcracks, and in severe cases, even shattering into pieces, making it impossible to peel completely off the release substrate, let alone meet the clinical requirements for flexible shielding films.
[0004] In high-solids coating systems, to suppress film cracking, existing technologies typically employ adjusting the system pH to a strongly alkaline range (>10.0). The theoretical basis for this is that an alkaline environment promotes the ionization of hydroxyl groups in PVA molecular chains, enhancing chain extension and crystal density. However, through extensive experimental research, the inventors have discovered that directly applying this pH adjustment strategy to medical coating materials leads to serious biosafety defects not addressed in existing technologies: while maintaining pH >10.0 by simply adding conventional alkaline substances such as sodium hydroxide and ammonia can achieve ideal film-forming effects, the measured pH values of the final product extract are generally above 10.0, significantly exceeding the safety limits (4.5–8.5) for the pH of extracts from intact skin contact devices as specified in ISO 10993-1:2018 and GB / T 16886.1-2022, thus failing to meet medical-grade biosafety requirements.
[0005] Existing technologies have attempted to improve the film-forming process by reducing the amount of alkali used, adding a buffer system, or acid washing and neutralization after film formation. However, these methods are impractical due to a sharp decline in film quality or excessive complexity. Therefore, how to ensure excellent film-forming properties—such as a complete, crack-free coating that can be peeled off as a whole—while maintaining a solid content as high as 70 wt%, and ensuring that the final product's pH value strictly meets medical safety standards, has long been a technical challenge for those skilled in the art. Summary of the Invention
[0006] This invention addresses the contradiction between the overall strongly alkaline environment (pH>10.0) required for film formation and the medically safe pH range (4.5–8.5) in existing high-solids-content radiation protection coatings containing PVA, as well as the problem of drying cracking of coatings with high solids content (≥70wt%). This invention provides a radiation protection coating and its preparation method.
[0007] One of the technical solutions of this invention is to propose a strategy for targeted regulation of interfacial activity: Inorganic radiation shielding materials are surface-etched and activated in a 0.2–1.5 mol / L inorganic alkaline aqueous solution at 25–80°C to generate dense hydroxyl groups; then, free alkali is removed by centrifugation and washing, with the final pH controlled at 8.0–10.0, to obtain a surface-functionalized activated filler. This filler is then compounded with PVA adhesive, where its surface hydroxyl groups form a high-density hydrogen-bonded cross-linking network with the PVA molecular chains. During drying, these hydroxyl groups act as physical cross-linking points, inducing orderly crystallization of PVA and effectively releasing shrinkage stress. This allows for the complete film formation of an ultra-high solids content coating of 70–85 wt% within a pH range of 4.5–8.5 without the need for a strong alkali solution. The coating can be peeled off entirely, exhibiting both excellent film-forming properties and medical-grade biosafety, making it suitable for applications such as medical radiation protection dressings, interventional surgical shielding coatings, and nuclear facility protection.
[0008] Specifically, the radiation-proof coating of the present invention comprises, by weight, the following components: 2-7 parts of polyvinyl alcohol, 1-3 parts of humectant, 5-13 parts of volatile agent, 5-15 parts of deionized water, and 70-85 parts of inorganic radiation-proof material with dense hydroxyl groups on the surface.
[0009] Inorganic radiation shielding material is dispersed in an inorganic alkaline aqueous solution and surface etched and activated at 25–80°C to obtain an activated slurry. The activated slurry is subjected to solid-liquid separation to obtain a precipitate. The precipitate is repeatedly washed to remove free alkali until the pH of the washing supernatant is 8.0–10.0, resulting in a filter cake. The filter cake is dried to obtain an inorganic radiation shielding material with dense hydroxyl groups on its surface. Polyvinyl alcohol, humectant, volatile agent, and deionized water are mixed evenly in proportion and heated to 60–95°C and stirred until completely dissolved to form a transparent liquid. The mixture is then cooled to room temperature. The radiation shielding material with dense hydroxyl groups on its surface is added to the transparent liquid and stirred to form a uniform paste. After vacuum degassing, the radiation shielding coating is obtained.
[0010] The core mechanism by which this invention achieves high film-forming properties lies in the following: After etching and activation with an inorganic alkaline aqueous solution, a large number of active hydroxyl groups (-OH) are generated on the surface of the inorganic radiation shielding material. The static water contact angle is significantly reduced from >110° before treatment to 70-90°, and the surface polarity is greatly enhanced. In the near-neutral compound system, the dense hydroxyl groups on the surface of the activated particles form a high-density intermolecular hydrogen bond cross-linking network with the hydroxyl groups on the PVA molecular chains. This network plays a dual role in the coating drying process: on the one hand, it acts as a physical cross-linking point, inducing the orderly arrangement of PVA molecular chains and promoting ordered crystallization, thereby improving the cohesive strength of the film layer; on the other hand, the uniformly distributed strong interfacial bonding can effectively transfer and buffer the shrinkage stress generated by solvent evaporation, thus macroscopically and thoroughly inhibiting the initiation and propagation of cracks. Even with a solid content as high as 85wt%, this interfacial mechanism can still ensure the integrity and flexibility of the film layer.
[0011] The key role of pH control at the end of the supernatant washing process in this invention is twofold: firstly, to ensure that a large amount of free alkali is removed, thus avoiding pH exceeding the standard in the final product; secondly, the pH of the supernatant at the end of the washing process is 8.0 to 10.0, which precisely avoids the isoelectric point of the oxide ceramic particles (usually between pH 6 and 8), allowing the particle surface to maintain a suitable deprotonated state and negative charge, effectively preventing hard agglomeration of particles during washing and drying, and maximizing the interfacial efficiency of retaining surface-active hydroxyl groups.
[0012] Because PVA is acidic, if the pH of the supernatant is less than 10, the final result after compounding will not exceed 8.5. The pH of the supernatant is greater than 8 because the isoelectric point of the oxide ceramic particles (usually between pH 6 and 8) needs to be avoided to prevent aggregation. The pH value of the anti-radiation coating extract of this invention is stable between 4.5 and 8.5 (4.5 to 8.5 is a safe range for skin dressings; all film-forming formulations of this invention have a final pH greater than 7 and less than 8.0, so this range is used). The key to this invention lies in abandoning the traditional "overall alkali adjustment" approach and adopting a "interface activation + precise alkali removal" strategy: First, repeated centrifugation and washing thoroughly remove residual free alkali from the filler surface until the pH of the supernatant at the washing endpoint is controlled at 8.0–10.0, which directly determines that the final product pH will not exceed 8.5; Second, during compounding, the weak acidity of the PVA adhesive itself is used to further neutralize the trace amounts of alkalinity remaining in the filler, ensuring that the final pH is stable at 7.0–8.0, and will not fall below 4.5; At the same time, the washing endpoint of the supernatant is deliberately controlled on the alkaline side (avoiding the isoelectric point region of pH 6–8), which prevents particle agglomeration, preserves the activity of surface hydroxyl groups, and avoids excessive washing leading to an excessively low pH. Because this invention achieves high-solids film formation by forming a hydrogen bond cross-linking network between the filler surface hydroxyl groups and PVA, there is no need to add additional alkaline substances such as NaOH to maintain an alkaline environment, so the pH of the final product extract naturally falls within the medical safety range.
[0013] The pH of the radiation-shielding coating is monitored by testing the pH of the supernatant. If the pH of the supernatant is greater than 10, it indicates that a large amount of free alkali has not been washed away. After compounding, the pH of the radiation-shielding coating formula will exceed 8.5, which does not meet safety requirements. If the pH of the supernatant is less than 10, as in Example 1, the pH of the supernatant after washing is 9.62, and the pH of the radiation-shielding coating formula is 7.54, which meets the requirements for film formation.
[0014] The inorganic alkaline aqueous solution is a sodium hydroxide solution or a potassium hydroxide solution, with a concentration of 0.2–1.5 mol / L, more preferably 0.5–1.0 mol / L; the ratio of the volume of the alkaline solution to the mass of the inorganic radiation shielding material is 0.5–2 L / kg.
[0015] In this invention, the inorganic radiation shielding material is one or more of bismuth tungstate, barium sulfate, bismuth oxide, tungsten oxide, gadolinium oxide, and their composites or mixtures; the particle size of the inorganic radiation shielding material is 1-70 μm.
[0016] In this invention, the inorganic alkaline aqueous solution is a sodium hydroxide solution or a potassium hydroxide solution with a concentration of 0.2 to 1.5 mol / L, and the mass ratio of the inorganic alkaline aqueous solution to the inorganic radiation shielding material is 0.5 to 2 L / kg.
[0017] The surface etching activation treatment time is 0.5 to 4 hours, the stirring speed during the surface etching activation treatment is 200 to 600 rpm, the washing is centrifugal separation combined with repeated rinsing with deionized water, the drying is freeze drying or low temperature vacuum drying, and the drying temperature does not exceed 50°C.
[0018] The moisturizer is one or more of glycerin, propylene glycol, sodium hyaluronate, and sorbitol.
[0019] The volatile agent is anhydrous ethanol.
[0020] The radiation-proof coating is applied to medical radiation protection dressings, local radiation shielding coatings for interventional surgery, or protective coatings for nuclear facilities such as nuclear power plants and nuclear reactors.
[0021] Compared with the prior art, the present invention has the following advantages: 1) The radiation protection coating of the present invention is a high solids content radiation protection coating, which is particularly suitable for medical radiation protection dressings, local radiation shielding coatings for interventional surgery, and protective coatings for nuclear facilities.
[0022] 2) The radiation-proof coating of the present invention is a radiation-proof coating based on surface-activated inorganic fillers. The present invention starts from the bottom interface mechanism of strengthening film-forming properties, aiming to simultaneously achieve "perfect film formation under high solid content" and "medical-grade pH safety".
[0023] 3) This invention abandons the traditional mindset of "adjusting alkali in the whole system" and starts from the interface of solid packing.
[0024] 4) Under extreme conditions with a total solids content as high as 70-85 wt%, the film formed by this invention has a uniform, continuous, smooth, and flat surface without any visible or microscopic cracks, and can be easily and completely peeled off from the release substrate. Experimental data shows that the maximum tensile force of the film can reach 2.56 N.
[0025] 5) The pH value of the radiation-proof coating extract of the present invention is stable at 4.5 to 8.5, which perfectly meets the pH requirements (4.5 to 8.5) for intact skin contact materials in ISO 10993-1:2018 and GB / T 16886.1-2022, and has medical-grade biosafety.
[0026] 6) The method for preparing the radiation-proof coating of the present invention ensures the complete removal of free alkali on the surface of each batch of particles and the stability of the activated state by controlling the pH at the washing endpoint; by monitoring the hydrophilicity and hydrophobicity (contact angle) of the surface, it provides clear quality control indicators for the process and is highly feasible for industrial-scale production.
[0027] 7) XRD analysis of the radiation shielding coating of the present invention shows that the diffraction peak positions and peak shapes of the inorganic radiation shielding material before and after surface activation treatment are basically the same, the crystal structure has not changed, and the radiation shielding function is completely preserved. Attached Figure Description
[0028] Figure 1 This is a comparison diagram of the water contact angle before and after the surface activation treatment of bismuth oxide powder in Example 1.
[0029] Figure 2 This is a schematic diagram comparing the X-ray diffraction (XRD) spectra of bismuth oxide powder before and after surface activation treatment in Example 1. Detailed Implementation
[0030] The following examples are provided to further illustrate the present invention and are intended to explain the invention, not to limit its scope. Unless otherwise specified, all figures are expressed in parts by weight and weight percentages.
[0031] Unless otherwise specified, the raw materials used in this invention are all conventional commercially available products; unless otherwise specified, the methods used in this invention are all conventional methods in the field.
[0032] The embodiments of the present invention will be further described below with reference to several examples.
[0033] It should be understood that the described embodiments are merely some, not all, of the embodiments in this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application without inventive effort are within the scope of protection of this application.
[0034] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0035] See Figures 1-2 This invention addresses the technical problem that existing radiation-proof coatings containing high solids content (≥70wt%) of polyvinyl alcohol (PVA) have poor film integrity and require strong overall alkalinity (pH>10.0) to form a film, resulting in the final product's pH level significantly exceeding the medical safety range (4.5~8.5).
[0036] This invention provides a radiation-shielding coating, comprising the following components by weight: 2-7 parts polyvinyl alcohol, 1-3 parts humectant, 5-13 parts volatile agent, 5-15 parts deionized water, and 70-85 parts inorganic radiation-shielding material with dense hydroxyl groups on its surface; the total solid content of the radiation-shielding coating is 70-85 wt%; the pH value of the radiation-shielding coating is 4.5-8.5; and the radiation-shielding coating, after being coated into a film, has a complete continuous film structure and can be peeled off as a whole.
[0037] Inorganic radiation shielding material is dispersed in an inorganic alkaline aqueous solution and surface etched and activated at 25–80°C to obtain an activated slurry. The activated slurry is subjected to solid-liquid separation to obtain a precipitate. The precipitate is repeatedly washed to remove free alkali until the pH of the washing supernatant is 8.0–10.0, resulting in a filter cake. The filter cake is dried to obtain an inorganic radiation shielding material with dense hydroxyl groups on its surface. Polyvinyl alcohol, humectant, volatile agent, and deionized water are mixed evenly in proportion and heated to 60–95°C and stirred until completely dissolved to form a transparent liquid. The mixture is then cooled to room temperature. The radiation shielding material with dense hydroxyl groups on its surface is added to the transparent liquid and stirred to form a uniform paste. After vacuum degassing, the radiation shielding coating is obtained.
[0038] In the following examples and comparative examples, all raw materials used were commercially available analytical grade reagents; the PVA used was polyvinyl alcohol with a degree of alcoholysis of 88% and a degree of polymerization of 500.
[0039] Performance testing methods: (1) Film integrity: The coatings obtained in each example and comparative example were uniformly coated on a polytetrafluoroethylene board with a wet film thickness of 300 μm and dried at 25°C and 50% relative humidity for 24 hours. The macroscopic morphology of the film layer was observed. If the film layer surface is uniform and continuous, without visible cracks and can be peeled off from the substrate as a whole, it is judged as "film integrity"; if there are through cracks or fragments, and it cannot be peeled off from the substrate as a whole, it is judged as "cracking".
[0040] pH measurement: Take an appropriate amount of sample and measure it directly with a pH meter.
[0041] (3) Mechanical property test: A paste film was prepared on a polytetrafluoroethylene plate using a 0.3 mm wire bar applicator and then cured at 37°C. The resulting film was cut into 50 mm × 15 mm strips and its maximum tensile force (N) was determined using a universal tensile testing machine.
[0042] (4) Surface hydrophilicity and hydrophobicity test: The powder sample was pressed into a sheet using the tablet-drop method, and the static water contact angle was measured using a contact angle meter.
[0043] (5) Phase analysis: X-ray diffractometer (XRD) was used to analyze the phase of inorganic radiation shielding material powder before and after surface activation treatment.
[0044] Figure 1 (a) shows the untreated raw bismuth oxide powder with a contact angle of 134°; (b) shows the bismuth oxide powder after being etched and activated by the alkaline solution of this invention and then washed and dried, with the contact angle reduced to 87°.
[0045] Figure 2In the image (a), the XRD pattern of the untreated raw bismuth oxide powder is shown, and in the image (b), the XRD pattern of the bismuth oxide powder after being etched and activated by the alkaline solution of this invention and then washed and dried is shown.
[0046] Figure 1 This indicates that the surface of the radiation-shielding coating becomes more hydrophilic (and the hydroxyl group density increases) after alkalization, and the contact angle reflects the hydroxyl groups (hydrophilicity) on the material surface; the XRD shows no change, indicating that alkalization has no significant effect on the structure. Specific details are described in the test results of Example 1.
[0047] Example 1 S1: Surface activation treatment: Weigh 100g of bismuth oxide powder and disperse it in 100mL of 1.0mol / L sodium hydroxide aqueous solution (the mass ratio of alkali solution to bismuth oxide is 1L / kg). Stir at 400rpm at 60°C for 2 hours to obtain activated slurry.
[0048] S2: Washing and Drying: The activated slurry was centrifuged, the supernatant was discarded, and the precipitate was repeatedly washed with deionized water by centrifugation. The pH of the supernatant was measured after each wash until the pH of the supernatant after the last wash was 9.62. The filter cake was collected and freeze-dried at -80°C for 24 hours to obtain surface-activated bismuth oxide powder.
[0049] S3: PVA adhesive preparation: Weigh 4 parts PVA, add 2 parts glycerin, 9 parts anhydrous ethanol and 10 parts deionized water in sequence, heat to 90°C and stir until completely dissolved to form a transparent adhesive, then cool to room temperature.
[0050] S4: Compounding: Add 75 parts of the surface-activated bismuth oxide powder obtained in step S2 to the above PVA adhesive, stir to form a uniform paste, and obtain the finished product after vacuum degassing. The total solids content of the coating is 75 wt%.
[0051] Test results of Example 1: After film formation, the film surface is uniform and continuous, without any cracks or fracture defects, and can be completely torn off from the polytetrafluoroethylene plate with a maximum force of 2.56 N. The pH of the final product extract is 7.54, which meets the medical safety pH range (4.5–8.5). After surface activation treatment, the static water contact angle of the bismuth oxide powder decreased from 134° before treatment to 87°, indicating that the surface changed from hydrophobic to hydrophilic, and the density of active hydroxyl groups was significantly increased. Figure 1 XRD analysis showed that the diffraction peak positions and shapes of bismuth oxide before and after activation treatment were basically the same, the crystal structure remained unchanged, and the X-ray shielding function was completely preserved. Figure 2 ).
[0052] Example 2 S1: Surface activation treatment: Weigh 100g of bismuth tungstate powder and disperse it in 200mL of 0.2mol / L potassium hydroxide aqueous solution (the mass ratio of alkali solution to bismuth tungstate is 2.0L / kg). Stir at 600rpm at 40°C for 0.5 hours to obtain activated slurry.
[0053] S2: Washing and Drying: The activated slurry was centrifuged, the supernatant was discarded, and the precipitate was repeatedly washed with deionized water by centrifugation until the pH of the supernatant after the last wash was 9.20. The filter cake was collected and vacuum dried at 50°C for 12 hours to obtain surface-activated bismuth tungstate powder.
[0054] S3: PVA adhesive preparation: Weigh 2 parts PVA, add 2 parts sorbitol, 6 parts anhydrous ethanol and 5 parts deionized water in sequence, heat to 80°C and stir until completely dissolved to form a transparent adhesive, then cool to room temperature.
[0055] S4: Compounding: Add 85 parts of the surface-activated bismuth tungstate powder obtained in step S2 to the above PVA adhesive, stir to form a uniform paste, and obtain the finished product after vacuum degassing. The total solids content of the coating is 85 wt%.
[0056] Test results of Example 2: After film formation, the film surface is uniform and continuous, without cracks, and can be peeled off as a whole. The pH of the final product extract is 7.12, which meets medical safety standards. The water contact angle of the activated bismuth tungstate powder decreased from 115° before treatment to 72°.
[0057] Example 3 S1: Surface activation treatment: Weigh a mixture of 50g gadolinium oxide powder and 50g tungsten oxide powder (mass ratio 1:1), disperse it in 50mL of 1.5mol / L sodium hydroxide aqueous solution (the mass ratio of alkali solution to mixed powder is 0.5L / kg), and stir at 200rpm at 50°C for 4 hours to obtain activated slurry.
[0058] S2: Washing and Drying: The activated slurry is centrifuged, the supernatant is discarded, and the precipitate is repeatedly washed with deionized water by centrifugation until the pH of the supernatant after the last wash is 8.59. The filter cake is collected and freeze-dried at -80°C for 30 hours to obtain surface-activated composite powder.
[0059] S3: PVA adhesive preparation: Weigh 7 parts PVA, add 1 part glycerin, 2 parts propylene glycol, 5 parts anhydrous ethanol and 15 parts deionized water in sequence, heat to 88°C and stir until completely dissolved to form a transparent adhesive, then cool to room temperature.
[0060] S4: Compounding: Add 70 parts of the surface-activated composite powder obtained in step S2 to the above PVA adhesive, stir to form a uniform paste, and obtain the finished product after vacuum degassing. The total solids content of the coating is 70 wt%.
[0061] Test results of Example 3: After film formation, the film surface is uniform and continuous, without cracks, and can be torn off as a whole, with a maximum force value of 2.31N. The pH of the final product extract is 7.05, which meets medical safety standards. The water contact angle of the activated composite powder decreased from 112° before treatment to 78°.
[0062] Example 4 S1: Surface activation treatment: Weigh 100g of barium sulfate powder and disperse it in 100mL of 1.0mol / L sodium hydroxide aqueous solution (the mass ratio of alkali solution to barium sulfate is 1L / kg). Stir at 600rpm for 1 hour at 60°C to obtain activated slurry.
[0063] S2: Washing and Drying: The activated slurry was centrifuged, the supernatant was discarded, and the precipitate was repeatedly washed with deionized water by centrifugation until the pH of the supernatant after the last wash was 8.98. The filter cake was collected and freeze-dried at -80°C for 30 hours to obtain surface-activated barium sulfate powder.
[0064] S3: PVA adhesive preparation: Weigh 3 parts PVA, add 1 part sodium hyaluronate, 13 parts anhydrous ethanol and 13 parts deionized water in sequence, heat to 88°C and stir until completely dissolved to form a transparent adhesive, then cool to room temperature.
[0065] S4: Compounding: Add 70 parts of the surface-activated barium sulfate powder obtained in step S2 to the above PVA adhesive, stir to form a uniform paste, and obtain the finished product after vacuum degassing. The total solids content of the coating is 70 wt%.
[0066] Test results of Example 4: After film formation, the film surface is uniform and continuous, without cracks, and can be peeled off as a whole. The pH of the final product extract is 7.76, which meets medical safety standards. The water contact angle of the activated barium sulfate powder decreased from 110° before treatment to 70°.
[0067] Comparative Example 1 (Alkali treatment but insufficient alkali removal) Preparation method: Except for the difference in the washing endpoint control in step S2, the remaining steps are exactly the same as in Example 1. In this comparative example, the activated slurry was washed only twice with deionized water after centrifugation. The pH of the supernatant from the last wash was 10.24, at which point washing was stopped and the slurry was directly freeze-dried. The resulting powder was then compounded with PVA adhesive according to steps S3-S4 of Example 1.
[0068] Test results for Comparative Example 1: After film formation, the film surface is uniform and continuous, without cracks, and can be peeled off as a whole. However, the pH of the final product extract is 8.86, exceeding the medical safety pH range (4.5–8.5). This result indicates that although a strongly alkaline overall system can improve film integrity, the pH of the final product is severely out of standard, failing to meet the safety requirements for medical materials.
[0069] Comparative Example 2 (Direct compounding of untreated fillers) Preparation method: The surface activation treatment and washing and drying processes in steps S1 and S2 are omitted. The raw bismuth oxide powder without any treatment is directly compounded with PVA adhesive according to steps S3 to S4 of Example 1.
[0070] Test results for Comparative Example 2: After coating and drying, the rapid evaporation of the solvent within the film layer generated significant capillary shrinkage stress. Combined with the physical obstruction of PVA molecular chain movement by the high content of rigid filler particles, this resulted in dense, penetrating microcracks in the film layer, causing severe fragmentation and making it completely impossible to peel off from the release substrate. Tensile strength could not be tested. The pH of the final product's extraction solution was 6.85 (which meets medical safety standards, but film-forming properties were completely lost). These results indicate that the unactivated hydrophobic inorganic filler lacks effective interfacial bonding with the PVA matrix, failing to form a hydrogen-bonded cross-linked network to buffer drying shrinkage stress. Comparative Example 3 (Composite after acid treatment of filler) Preparation method: 100g of bismuth oxide powder was dispersed in 100mL of 1.0mol / L acetic acid aqueous solution and stirred at 400rpm for 2 hours at 60°C. Then, it was centrifuged, washed with deionized water until the pH of the washing supernatant was 6.50, freeze-dried, and then compounded with PVA adhesive according to steps S3 to S4 of Example 1.
[0071] Test results for Comparative Example 3: After coating and drying, the film layer exhibited severe cracking, failing to form a complete film structure and unable to be peeled off the substrate. The pH of the final product extract was 5.92 (meeting medical safety standards, but film-forming properties failed). These results indicate that acid treatment cannot effectively generate dense active hydroxyl groups on the surface of the inorganic filler, and sufficient hydrogen bond crosslinking points cannot be formed between the filler and the PVA matrix to resist drying shrinkage stress.
[0072] Comparative Example 4 (untreated filler, PVA adhesive pH pre-adjusted to strongly alkaline) Preparation method: The surface activation treatment and washing and drying processes in steps S1 and S2 are omitted. The untreated raw bismuth oxide powder is directly compounded with PVA adhesive according to steps S3 and S4 of Example 1. NaOH is added to pre-adjust the pH of the coating to 9.31 and 10.20, respectively.
[0073] Test results for Comparative Example 4: Testing revealed that when the overall pH of the coating system was only 9.30, the film layer could not be completely peeled off from the substrate after coating and drying. However, when the pH of the system was increased to 10.20, the resulting film layer had a uniform and continuous surface without cracks or defects, and exhibited good overall peelability. Comparative Example 4 showed that while simply increasing the pH of the system could improve film integrity, the final product pH (10.20) significantly exceeded the medical safety range (4.5–8.5), failing to meet clinical application requirements. In contrast, the interfacial hydrogen bond crosslinking network constructed by the filler surface activation of this invention achieved equally complete film formation under neutral to weakly alkaline conditions (Example 1, pH 6.99), fully demonstrating that overall strong alkalinity is not a necessary condition for film formation. Adding additional alkali sacrifices the biosafety of the product and is therefore a pointless endeavor.
[0074] Comparative Example 5 (pH too low at the end of washing after activation) Preparation method: Except for the different control of the washing endpoint in step S2, the other steps are exactly the same as in Example 1. In this comparative example, the activated slurry was repeatedly centrifuged and washed with deionized water until the pH of the supernatant from the last wash was 7.50. The filter cake was collected and freeze-dried, and then compounded with PVA adhesive according to steps S3 to S4 of Example 1.
[0075] The test results of Comparative Example 5: After coating and drying, the film layer showed obvious cracks and could not be completely peeled off from the substrate. The pH of the final product extract was 6.82 (meeting medical safety standards, but film-forming properties failed). This result indicates that when the washing endpoint pH is too low (close to or below the isoelectric point of the filler), severe hard agglomeration occurs on the particle surface, the interfacial efficiency of the active hydroxyl groups is greatly reduced, and they cannot form a sufficient hydrogen bond crosslinking network with PVA.
[0076] Summary of Results from Examples and Comparative Examples As shown in the table above, Comparative Examples 2 (untreated filler) and 3 (acid-treated filler) suffered from severe film cracking at high solids content because the filler surface lacked active hydroxyl groups, preventing the formation of sufficient hydrogen bond cross-linking networks with PVA. Comparative Example 1, while capable of film formation, resulted in a final product with excessive pH. Comparative Example 4 also faced the problem of excessive pH, and film formation was positively correlated with pH, indicating that overall strong alkalinity is a necessary condition for film formation in existing technologies. Comparative Example 5 suffered from particle agglomeration due to excessively low pH at the washing endpoint, resulting in loss of the interfacial effectiveness of active hydroxyl groups and film formation failure. Only Examples 1-3 of this invention, through a synergistic strategy of "surface etching activation - precise control of washing endpoint - pH neutral compounding," constructed and effectively retained dense active hydroxyl groups on the filler surface, forming a high-density hydrogen bond cross-linking network with PVA molecular chains. This achieved perfect film formation of high solids content (70-85 wt%) coatings without the need for overall strong alkalinity, while the final product pH strictly met medical safety standards.
[0077] The above embodiments describe in detail the structure, features, and effects of the present invention. The above description is only a preferred embodiment of the present invention. Any changes made in accordance with the concept of the present invention, or equivalent embodiments modified to have equivalent changes, shall still fall within the scope of protection of the present invention if they do not exceed the scope covered by the specification.
[0078] Although embodiments of the invention have been disclosed for illustrative purposes, those skilled in the art will understand that various substitutions, variations, and modifications are possible without departing from the spirit and scope of the invention and the appended claims. Therefore, the scope of the invention is not limited to the contents disclosed in the embodiments.
Claims
1. A radiation-shielding coating, characterized in that, The coating comprises, by weight, the following components: 2-7 parts polyvinyl alcohol, 1-3 parts humectant, 5-13 parts volatile agent, 5-15 parts deionized water, and 70-85 parts inorganic radiation shielding material with dense hydroxyl groups on its surface; the total solid content of the radiation shielding coating is 70-85 wt%; the pH value of the radiation shielding coating is 4.5-8.5; and the radiation shielding coating, after being coated into a film, has a complete continuous film structure and can be peeled off as a whole.
2. The radiation-shielding coating according to claim 1, characterized in that, The inorganic radiation shielding material with dense hydroxyl groups on its surface is obtained by dispersing the inorganic radiation shielding material in an inorganic alkaline aqueous solution, performing surface etching activation treatment at 25-80°C to obtain an activated slurry, performing solid-liquid separation on the activated slurry to obtain a precipitate, repeatedly washing the precipitate to remove free alkali until the pH of the washing supernatant is 8.0-10.0, obtaining a filter cake, and drying the filter cake to obtain the inorganic radiation shielding material with dense hydroxyl groups on its surface.
3. The radiation-shielding coating according to claim 2, characterized in that, The inorganic radiation shielding material is one or more of bismuth tungstate, barium sulfate, bismuth oxide, tungsten oxide, gadolinium oxide, and their composites or mixtures; the particle size of the inorganic radiation shielding material is 1-70 μm.
4. The radiation-shielding coating according to claim 3, characterized in that, The inorganic alkaline aqueous solution is a sodium hydroxide solution or a potassium hydroxide solution with a concentration of 0.2–1.5 mol / L, and the mass ratio of the inorganic alkaline aqueous solution to the inorganic radiation shielding material is 0.5–2 L / kg.
5. The radiation-shielding coating according to claim 4, characterized in that, The surface etching activation treatment time is 0.5 to 4 hours, the stirring speed during the surface etching activation treatment is 200 to 600 rpm, the washing is centrifugal separation combined with repeated rinsing with deionized water, the drying is freeze drying or low temperature vacuum drying, and the drying temperature does not exceed 50°C.
6. The radiation-shielding coating according to claim 5, characterized in that, The moisturizer is one or more of glycerin, propylene glycol, sodium hyaluronate, and sorbitol.
7. The radiation-shielding coating according to claim 6, characterized in that, The volatile agent is anhydrous ethanol.
8. A method for preparing the radiation-shielding coating according to any one of claims 1 to 7, characterized in that, Inorganic radiation shielding material is dispersed in an inorganic alkaline aqueous solution and surface etched and activated at 25–80°C to obtain an activated slurry. The activated slurry is subjected to solid-liquid separation to obtain a precipitate. The precipitate is repeatedly washed to remove free alkali until the pH of the washing supernatant is 8.0–10.0, resulting in a filter cake. The filter cake is dried to obtain an inorganic radiation shielding material with dense hydroxyl groups on its surface. Polyvinyl alcohol, humectant, volatile agent, and deionized water are mixed evenly in proportion and heated to 60–95°C and stirred until completely dissolved to form a transparent liquid. The mixture is then cooled to room temperature. The radiation shielding material with dense hydroxyl groups on its surface is added to the transparent liquid and stirred to form a uniform paste. After vacuum degassing, the radiation shielding coating is obtained.
9. The method for preparing the anti-radiation coating according to claim 8, characterized in that, The radiation-proof coating is applied to medical radiation protection dressings, local radiation shielding coatings for interventional surgery, or protective coatings for nuclear facilities such as nuclear power plants and nuclear reactors.